Characterization of Physicochemical Parameters of Textile Effluents and Its Impacts on Environment - Nirmala Chockalingam; Sambhasan Banerjee; Sridevi Muruhan (Environment and Natural Resources Journal, 2019)
Globally, textile industries play an important role in the economy of many countries. A huge volume of water is consumed in the various processes of dyeing fabrics and the majority of this is discharged with heavy loads of pollutants into the environment. The present study assessed the physicochemical characteristics of textile effluents from different areas of Salem, Tamil Nadu, India, where the city groundwater quality has decreased with increasing industrialization. The parameters of colour, pH and total hardness, biological oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), chlorides, oil and grease were analyzed. Almost all the parameters were above the permissible limits set by the Bureau of Indian Standards (BIS). The high value of the pollutants shows that the effluents are discarded without proper treatment which may provoke hazardous effects on terrestrial and aquatic ecology and poses potential threats to the local environment. Although many conventional effluent treatment methods are implemented in many places, additional technologies still need to be developed for the complete removal of the pollution load.